Pengembangan Cyber Counseling Sebagai Inovasi Baru Dalam Layanan Bimbingan dan Konseling (Prosiding Konseling Kearifan Nusantara (KKN), 2024)
The aim of writing this article is to find out the counseling process services using the Cyber-counseling method. Cyber-counseling is a counseling process a counselor offers to a counselee via electronic media with internet support. This cyber-counseling can be done effectively without having the counselor and counselee carry out the counseling process directly, regardless of distance. Cyber-counseling has advantages such as high accessibility, time and cost efficiency, and diversity of choices. However, cyber-counseling also has weaknesses, namely that the relationship between counselor and counselee cannot be direct and data confidentiality is not good. This Cyber-counseling method is recommended for counselors who cannot meet directly with counselees and for counselees who cannot undergo the counseling process if they have to meet with the counselor in person